The occurrence and influencing factors of fatigue and sleep disturbance in maintenance hemodialysis patients - Dong Kaixuan; Chen Xi; Zhou Rong; Yu Xiaoyong (Archives of Clinical Nephrology - Peertechz Publications, 2022)
Objective: To investigate the occurrence and influencing factors of fatigue and sleep disturbance in Maintenance Hemodialysis (MHD) patients.  Methods: A total of 170 patients with end-stage renal disease who underwent MHD treatment in the hemodialysis room of Shaanxi Provincial Hospital of Traditional Chinese Medicine from October 2021 to March 2022 were selected as the research subjects. The basic information and laboratory indicators of the patients were collected by cross-sectional survey. The survey methods were evaluated by the revised Piper Fatigue Scale and the Pittsburgh Sleep Quality Rating Scale and the incidence and influencing factors of fatigue and sleep disturbance in MHD patients were analyzed.  Results: Fatigue occurred in 135 cases, the incidence rate was 79.41%; sleep disturbance occurred in 124 cases and the incidence rate was 72.94%. After one-way analysis of variance, factors such as exercise, Albumin (ALB, serum Creatinine(CRE), Phosphorus(P) and Hemoglobin(HGB) in MHD patients can affect fatigue; while age, gender, exercise, primary disease, dialysis frequency, Phosphorus(P), Hemoglobin(HGB) and high-sensitivity C-Reactive Protein (hs-CRP) factors can affect sleep. A multiple linear regression model was constructed for the factors affecting fatigue (F = 81.110, p < 0.001), and it showed that 70.3% of fatigue (adjusted R2 = 0.703) was related to albumin (ALB), serum creatinine(CRE), and hemoglobin(HGB) (all p < 0.05); A multiple linear regression model was constructed based on the factors of 58% (F = 26.933, p < 0.001), which showed that 58% of sleep disorders (adjusted R2 = 0.580) were significantly related to age, gender, exercise or not, phosphorus(P), high-sensitivity C-reactive protein(hs-CRP) (all p < 0.05) related. Pearson correlation analysis was used to analyze sleep disturbance and fatigue in MHD patients and the results showed that there was a positive correlation between the two (r = 0.478, p < 0.001).  Conclusion: The proportion of fatigue and sleep disturbance in MHD patients is relatively high, mainly mild to moderate and the two influence each other. Exercise intervention and nutritional support can effectively improve the occurrence of fatigue and sleep disturbance in MHD patients.